EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TAI BERBASIS AFL PADA PERSAMAAN GARIS LURUS DITINJAU DARI SIKAP SISWA TERHADAP MATEMATIKA - Nurcahyo, Adi; Budiyono, Budiyono; Usodo, Budi (Journal of Mathematics and Mathematics Education, 2016)
Abstract: The purpose of this research was to determine the effect of learning models on mathematics achievement viewed from student attitude toward mathematics. The learning models compared were Team Assisted Individualization (TAI) based Assessment for Learning (AfL), TAI, and conventional learning model. The research was quasi experimental. The population of this research was all students of grade VIII State Junior High School of the District Karanganyar, academic year 2013/2014. The samples in this research were SMPN 1 Tasikmadu, SMPN 2 Jaten, and SMPN 2 Colomadu taken by stratified cluster random sampling. Instruments used to collect data were mathematics achievement instrument test and questionnaires students toward mathematics instrument. Data analysis technique used hypothesis test with two-way analysis of variance with unbalanced cells. From the results of the analysis, can be concluded that: 1) the learning achievement in mathematics of the students who were learning mathematics with cooperative learning model TAI Based AfL were better than the ones who were learning mathematics with cooperative learning model TAI and conventional learning model, however the students who were learning mathematics with cooperative learning model TAI were better than the ones who were learning mathematics with conventional learning model, 2) the learning achievement in mathematics of the students with the high attitude toward mathematics were better than the ones with the medium and low attitude toward mathematics, however the students with the medium  attitude toward mathematics were better  than the ones with the low attitude toward mathematics, 3) in the cooperative learning model TAI Based AfL, the learning achievement in mathematics of the students with ones who have the high attitude toward mathematics were better than the students with the low attitude toward mathematics, and students with the medium attitude toward mathematics were as good as the ones who have low attitude toward mathematics as well. In the cooperative learning model TAI and conventional learning model, the students with the high, medium, and low attitude toward mathematics had the same achievement in learning mathematics, 4) in the students with the high attitude toward mathematics, the learning achievement of the students who were learning mathematics with ones who have cooperative learning model TAI Based AfL were better than the students were learning mathematics with cooperative learning model TAI, the students who were learning mathematics with cooperative learning model TAI had the same achievement in learning mathematics with conventional learning model, and the students who were learning mathematics with cooperative learning model TAI Based AfL had the same achievement in learning mathematics with cooperative learning model TAI. The students with the medium and low attitude toward mathematics had the same achievement in learning mathematics among the ones who were given the cooperative learning model TAI Based AfL, TAI, and conventional learning model.Keywords: Team Assisted Individualization (TAI), Assessment for learning (AfL), students attitude toward mathematics, achievement learning mathematics.